The Collision Detection Algorithm in Virtual Reality - Zhao Wei; Guo Xinxin (2012 International Conference on Computer Science and Electronics Engineering, 2012)
This paper puts forward a kind of hybrid algorithm-combining the hierarchical bounding volume method and the bounding volume coordinate chain method in the virtual environment. This algorithm can improve the efficiency of collision detection, rigid body and the software both can be applied to with the collision detection. Then we built the task trees by traversing the mixed hierarchical bounding volumes and speeded up the collision detection algorithm by applying a parallel computing and introduce a space-time correlations concept to accelerate the speed of updating of the bounding box at the same time. Objects that intersect precisely in the testing process, combined with hierarchical bounding box tree compression and storage, storage space by reducing the algorithm to improve the detection algorithm speed. Experimental results show that the method compared with the single bounding method level, it advantages, and objects in the detection of more cases can reduce the execution time required for the algorithm.